Stability of and Change in Psychopathological Risk Levels in Pre-Early Adolescents before, during, and after Their Study Sojourns: A Descriptive Study - Luca Cerniglia; Silvia Cimino (MDPI AG, 2024)
Background: Adolescents can benefit from studying abroad in terms of personal development, cross-cultural encounters, and academic enrichment. This article digs into the psychological challenges that students may face before and during their study abroad, focusing on the emotional components of their experiences. Methods: The current descriptive study sought to assess the stability or change in levels of psychopathological risk in a sample of N = 195 adolescents before and during a study abroad sojourn. To examine psychological symptoms in pre-adolescents, teachers were asked to complete a report-form questionnaire. Results: The findings of this study revealed that students' psychological functioning changed significantly after their study abroad experience. Anxious/depressed and withdrawn ratings specifically increased from the pre-sojourn assessment (T1) to the evaluation during the stay (T2), then remained consistent (T3). In addition, the scores for rule-breaking and aggressive conduct changed, increasing from T1 to T2 and then decreasing from T2 to T3. This trend implies that teenagers may struggle with behavioral challenges early in their study abroad experience, but subsequently adjust and improve their conduct as they grow more used to the new environment. Conclusions: this research offers insight into the emotional and behavioral issues that adolescents face when studying abroad, underlining the significance of treating psychopathological risk factors in this demographic.